HOXB7 accelerates the malignant progression of hepatocellular carcinoma by promoting stemness and epithelial-mesenchymal transition - Huan, Hong-bo (J Exp Clin Cancer Res, 2017)
BACKGROUND: Homeobox B7 (HOXB7) has been identified associated with poor prognosis of hepatocellular carcinoma (HCC). However, the specific mechanism by which HOXB7 promotes the malignant progression of HCC remains to be determined. METHODS: Immunohistochemistry (IHC) was used to detect the expression level of HOXB7 in 77-paired HCC tissue samples, and the correlation between HOXB7 and HCC prognosis was assessed. The location of HOXB7 was confirmed by immunofluorescence. Cell Titer-Blue assay was used to assess the proliferation of hepatoma cells. The stem-like properties of hepatoma cells were analysed by sphere formation and clone formation assays. The effect of HOXB7 on expression of cancer stem cell markers was evaluated. Transwell and wound-healing assays were performed to estimate the invasion and migration abilities of hepatoma cells. A xenograft tumor model was established in nude mice to assess the role of HOXB7 in tumor growth. Bioluminescence imaging was used to survey the effect of HOXB7 on the metastatic ability of hepatoma cells in vivo. RESULTS: Higher expression of HOXB7 was detected in HCC tissues compared with noncancerous tissues and significantly associated with poor prognosis of HCC. In addition, HOXB7 knockdown suppressed the cell proliferation, clone formation, sphere formation, invasion and migration of hepatoma cells in vitro; conversely, these biological abilities of hepatoma cells were enhanced by HOXB7 overexpression. Moreover, the cancer stem cell markers EPCAM and NANOG were up-regulated by HOXB7. The role of HOXB7 in promoting tumor growth and metastasis was verified in vivo. Further investigation revealed that c-Myc and Slug expression was elevated by HOXB7 and the AKT pathway was activated. CONCLUSION: Overexpression of HOXB7 was significantly correlated with poor prognosis of HCC. HOXB7 up-regulated c-Myc and Slug expression via the AKT pathway to promote the acquisition of stem-like properties and facilitate epithelial-mesenchymal transition of hepatoma cells, accelerating the malignant progression of HCC.